2009
DOI: 10.1021/am900656y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Triaxial LiFePO4 Nanowire with a VGCF Core Column and a Carbon Shell through the Electrospinning Method

Abstract: A triaxial LiFePO4 nanowire with a multi wall carbon nanotube (VGCF:Vapor-grown carbon fiber) core column and an outer shell of amorphous carbon was successfully synthesized through the electrospinning method. The carbon nanotube core oriented in the direction of the wire played an important role in the conduction of electrons during the charge-discharge process, whereas the outer amorphous carbon shell suppressed the oxidation of Fe2+. An electrode with uniformly dispersed carbon and active materials was easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 29 publications
2
95
0
1
Order By: Relevance
“…A high electrochemical performance was also achieved at the elevated operating temperature of 60 °C, with such cells displaying stable cycling (C rate) close to the theoretical maximum; capacity retention was expressed as 98% of the initial capacity after 100 charge-discharge cycles [392]. The electrochemical performance of the single-crystalline LFP nanowires exceeded those of CNT-LFP tri-axial nanowire composites prepared by a similar electrospinning process [426]. The increased performance is attributed to the smaller diameter nanowires (~100 nm), versus the larger CNT-LFP composite (~500 nm), resulting in shorter Li + diffusion paths.…”
Section: Lifepo4 (Lfp)mentioning
confidence: 88%
See 1 more Smart Citation
“…A high electrochemical performance was also achieved at the elevated operating temperature of 60 °C, with such cells displaying stable cycling (C rate) close to the theoretical maximum; capacity retention was expressed as 98% of the initial capacity after 100 charge-discharge cycles [392]. The electrochemical performance of the single-crystalline LFP nanowires exceeded those of CNT-LFP tri-axial nanowire composites prepared by a similar electrospinning process [426]. The increased performance is attributed to the smaller diameter nanowires (~100 nm), versus the larger CNT-LFP composite (~500 nm), resulting in shorter Li + diffusion paths.…”
Section: Lifepo4 (Lfp)mentioning
confidence: 88%
“…The ~100 nm wires, which are smaller than those previously reported for LFP [426,427], were deposited on stainless steel substrates by electrospinning an aqueous solution of Fe(NO3)3, LiH2PO4 and poly(ethylene oxide) (PEO), using an accelerating voltage of 15 kV before thermal annealing at 700 °C under flowing N2. TEM analysis revealed that the LFP nanowires grew along the c-axis, leading to facile Li + transport and a potentially high-rate response along the shortened b-and a-axis, while the carbon coating ensured adequate electrical conductivity and minimal aggregation throughout the electrode.…”
Section: Lifepo4 (Lfp)mentioning
confidence: 99%
“…Hosono et al synthesized a triaxial LiFePO 4 nanowire with a vapor-grown carbon fiber (VGCF) core and an amorphous carbon shell by the electrospinning method. The carbon fiber core oriented in the direction of the wire plays an important role in the conduction of electrons, whereas the outer amorphous carbon shell suppresses the oxidation of Fe 2+ [10]. Murugan et al used a microwave irradiated solvothermal method to prepare single crystalline lithium metal phosphates LiMPO 4 (M = Mn, Fe, Co, and Ni) with nano-thumblike shapes.…”
Section: -D Cathode Materialsmentioning
confidence: 99%
“…Similarly, traditional tri-axial electrospinning always uses an electrospinnable outer fluid [32][33][34][35][36][37][38][39][40]. A modified tri-axial process focused on the exploitation of un-spinnable liquids has also been reported [28].…”
Section: Introductionmentioning
confidence: 99%